Pathway Linking Childhood Trauma to Loneliness in Individuals with Romantic Break-up Grief: The Mediating Roles of Attachment Styles and Ambivalence over Emotional Expression - Rasoul Heshmati; Roya Fathalizadeh; Mojtaba Ahmadi Farsani; Monica Pellerone (روانشناسی بالینی و شخصیت)
Introduction: Romantic grief is a common phenomenon that can result in various consequences for individuals, one of the most significant being feelings of loneliness. This study aims to explore the relationship between childhood trauma and feelings of loneliness in individuals experiencing grief from romantic breakups, while also examining the mediating roles of interpersonal attachment styles and ambivalence regarding emotional expression.Method: This study employs a descriptive, correlational, and cross-sectional research design. To meet the research objectives, a sample of 800 individuals was selected from the student population of Tabriz University using convenience sampling. Among these participants, 219 individuals who exhibited romantic break-up grief scores exceeding one standard deviation above the mean were identified as the primary sample for the study. The research instruments utilized in this study included the Childhood Trauma Questionnaire, the Revised Adult Attachment Scale, the Ambivalence over Emotional Expression Questionnaire, and the Social and Emotional Loneliness Scale for Adults. Data analysis was performed using Structural Equation Modeling (SEM).Results: The findings of the study suggest that childhood trauma, as hypothesized in the model, does not directly account for differences in feelings of loneliness. Instead, it can clarify these variations through mediating factors such as attachment styles and ambivalence towards emotional expression. Additionally, the results indicate that the proposed model demonstrates a good fit.Discussion and conclusion: The findings suggest that childhood trauma significantly contributes to the development of mental health issues, particularly feelings of loneliness in adulthood. The adverse effects of trauma experienced during the first five years of life can negatively impact an individual's mental well-being by influencing the formation of attachment styles and the expression of emotions.